Effect of cristobalite formation on the delamination resistance of an oxide/Si/(SiC/SiC) environmental barrier coating system after cyclic high temperature thermal exposure. (October 2017) - Arai, Yutaro; Aoki, Yuto; Kagawa, Yutaka
Abstract: Delamination toughness of a mullite/Si/(SiC/SiC) environmental barrier coating (EBC) system has been measured using a shear-loading test. The EBC system is initially heated to a temperature of 1470 °C (above the melting point of Si (1414 °C)), and then repeated thermal exposure is carried out at a temperature 1320 °C (below the melting point of Si) for 2 h/cycle. Change of the delamination toughness with heat exposure is successfully obtained using the shear-loading test. Formation of cristobalite and transformation from α ↔ β during thermal cycling cause an increase of crack density in the Si bond coat layer and a resulting reduction in delamination toughness. Graphical abstract: